(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
Education Quality (EQ) encompasses various factors influencing the effectiveness of an education system in achieving its learning objectives. This study assessed education quality in Military Base Secondary Schools (MBSS) in Kaduna State, Nigeria, using Canonical Correlation Analysis (CCA) on data from the 2020-2022 West Africa Senior Schools Certificate Examination (WASSCE). Factors analyzed included student performance in Mathematics, English Language, Chemistry, Physics, and Biology, and educational inputs such as student-teacher ratio (STR), average laboratory expenditure per student (AE), gender parity index for teachers (GPI), teachers’ teaching experience (TTE), and ratio of military to civilian staff (RMCS). Descriptive statistics showed significant disparities, notably in RMCS (mean = 16.73, SD = 18.65). A weak negative correlation (-0.217) between STR and AE and a moderate positive correlation (0.358) between TTE and GPI were found. A strong positive correlation (0.964) between Mathematics and English Language performance was also identified. The study highlighted that a higher proportion of military staff negatively impacts student performance, emphasizing the need for balanced staffing policies. The predictive model underscored the significant role of RMCS in education quality in MBSS The study recommends that military authorities and educational policymakers address staffing disparities, Efforts should ensure balanced staffing, optimize resource allocation for laboratory expenses, promote gender balance among teachers, and prioritize recruiting experienced educators. Additionally, integrated teaching approaches should reinforce the positive correlation between English language proficiency and mathematics performance.